2022
DOI: 10.1002/ep.13899
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of MgAl layered double oxides and its adsorption kinetics for ciprofloxacin hydrochloride in water

Abstract: Magnesium aluminum carbonate hydrotalcites (MgAl‐LDHs) were prepared by a coprecipitation method using magnesium nitrate and aluminum nitrate as raw materials, and then calcined at high temperature to obtain hydrotalcite‐like MgAl layered double oxides (MgAl‐LDOs). With ciprofloxacin hydrochloride as the target pollutant, and the adsorption kinetics of ciprofloxacin hydrochloride by MgAl‐LDOs were assessed. The results show that: MgAl‐LDHs and MgAl‐LDOs are both mesoporous adsorbent materials. After MgAl‐LDHs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…With the temperature increase, glutamate underwent gradual carbonization and eventually produced CO 2 and H 2 O. 45 The DTG curve indicated that the weight loss of the material before and after modification is divided into three primary stages. (I) 50–100 °C, the weight loss was mainly due to the physical adsorption of water on the surface of the material.…”
Section: Resultsmentioning
confidence: 99%
“…With the temperature increase, glutamate underwent gradual carbonization and eventually produced CO 2 and H 2 O. 45 The DTG curve indicated that the weight loss of the material before and after modification is divided into three primary stages. (I) 50–100 °C, the weight loss was mainly due to the physical adsorption of water on the surface of the material.…”
Section: Resultsmentioning
confidence: 99%
“…LDHs are good and affordable adsorbents for absorbing anionic contaminants from aqueous settings due to the exchangeability of interlayer anions. Recently, a research paper was published for the adsorptive removal of ciprofloxacin using MgAl LDH and maximum adsorption capacity was recorded as 112.72 mg/g …”
Section: Introductionmentioning
confidence: 99%